Controllability of nonlinear fractional Langevin delay systems - Kumar, Pitchaikkannu Suresh Suresh; Balachandran, Krishnan; Annapoorani, Natarajan (Nonlinear Analysis: Modelling and Control, 2019)
In this paper, we discuss the controllability of fractional Langevin delay dynamical systems represented by the fractional delay differential equations of order 0